Learning loss in English among the 9th Graders during the Emergency Remote Teaching - Purwaningsih, Ayuana; Lie, Anita (Beyond Words, 2024)
This cross-sectional study aims to investigate a possible learning loss among 9th grade students in the English language learning by comparing pre-pandemic and during pandemic samples and to discover its correlation with a-year implementation of emergency remote teaching/learning. During the Covid-19 pandemic, school closures have restricted regular learning activities and changed into learning from individual homes revealing a learning disparity. Limited access to digital infrastructure and parents’ inexperience in supporting children’s learning particularly in the lower socio-economic class hamper the students’ academic achievement. There have been concerns about possible learning loss. Therefore, it is urgent to investigate the possible learning loss among 9 graders in the English classrooms during the emergency remote teaching. A quantitative study with a survey research design was applied. The data were obtained by implementing the 2019 English National Examination and a questionnaire. Eighty-one 9th grade students of a state school and seventeen of a private school in Indonesia participated in this study. The data were analyzed using SPSS to reveal the comparison and correlation. The findings reveal a significant decrease in the obtained exam scores of the current subjects indicating a learning loss in the state and private school. It shows a correlation between students’ autonomous learning and learning barriers with learning loss